Cupriavidus gilardii infection following heart failure: a case report and literature review - Yanwen Liu; Jianxin Gao; Jingyun Ye; Hui Han; Haiyan Zhu (BMC Infectious Diseases)
Abstract Background Cupriavidus gilardii is a species of the genus Cupriavidus. Knowledge about the pathogenic characteristics of Cupriavidus gilardii is limited, especially cardiac infection with this bacterium has not been reported. Case presentation We encountered a case of pulmonary infection after myocardial infarction and heart failure. The initial empirical treatment with meropenem was ineffective. After cultured Cupriavidus gilardii, cefoperazone sulbactam and minocycline were used, and the infection and heart failure was improved for few days. Unfortunately, the patient eventually died of heart failure exacerbated by infection with Staphylococcus Epidermidis. Conclusion Meropenem has a limited therapeutic effect on this bacterium. Monitoring heart function and selecting effective antibiotics are crucial for improving the prognosis of patients suffered from heart disease and Cupriavidus gilardii infection.